Selling vertically differentiated products under one channel or two? A quality segmentation model for differentiated distribution channels. Issue 8 (2nd August 2020) - Chai, Junwu; Yan, Wei; Li, Youwei; Palmer, Mark; Huang, Qilin
Abstract: Many manufacturers have adopted differentiated distribution channels to market vertically differentiated products. However, there is scant literature addressing the quality differentiation in the presence of differentiated channel policies. We, therefore, examine whether (how) differentiated channel policies affect manufacturers' quality differentiation and all parties' performance. Specifically, we consider a manufacturer who produces high- and low products together, but with two marketing options: (1) distributing both products through one retailer (Model O), or (2) providing high quality products through one channel but low-tier products through another (Model T). Our results show that the manufacturer is more likely to decrease the level of quality differentiation in Model T than in Model O. Moreover, we show that "quality distortion" is not limited to low-tier products but can occur with high-tier products. We also comment on how the additional horizontal consumer heterogeneity affects our results and the implications of the competition at the manufacturer level.